(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article provides a comparative analysis of the experiences of improving the qualifications of preschool education leaders in the education systems of Finland, South Korea and Uzbekistan. In each country, programs aimed at training, retraining and developing their professional potential, management principles, pedagogical leadership models and organizational and pedagogical mechanisms of the qualification improvement process are studied. Finland’s innovative educational approaches, South Korea’s technological and systematic management model and Uzbekistan’s national experience, which is being formed on the basis of reforms in recent years, are compared.